Pengaruh Produk, Promosi Terhadap Citra Merek dan Implikasinya Terhadap Keputusan Pembelian Produk pada PT.XYZ - Vanny Eka Marini (Publikasi Indonesia, 2022)
This study aims to determine and analyze the effect of product quality and promotion on purchasing decisions through brand image as an intervening variable. The object of this research is customers who use PT.XYZ products. This research was conducted on 100 respondents using a quantitative descriptive approach using the IBM SPSS 23 application. Therefore, the data analysis used is statistical analysis in the form of multiple linear regression analysis. The results of this study indicate that product quality, promotion through brand image have an effect on purchasing decisions. This is evidenced by the results of multiple linear regression analysis which shows the significant value of the variables that support the hypothesis.